2005
DOI: 10.1258/0022215054020395
|View full text |Cite
|
Sign up to set email alerts
|

Deep neck abscess: a prospective study of 54 cases

Abstract: Deep neck abscesses (DNAs) continue to be commonly encountered in developing countries like India. This study was conducted to determine the changing trends within our population with respect to presentation, aetiology, location and microbiology of DNAs. Fifty-four patients with DNAs who were managed at the Department of ORL and H&N Surgery in our hospital between May 2002 and December 2002 formed the basis of the study. We observed that the high incidence of DNAs could be attributed to lack of awareness, illi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 4 publications
15
18
0
Order By: Relevance
“…Infections of masticator space, retropharyngeal space and parotid space were approximately 7% of our study. Our results were consistent with Meher (9) and Rega (20) with submandibular space as the most common location of DNSI in 37% and 30% of the patients. Our results were not consistent with following studies: Parhiscar study in which parapharyngeal space had the most involvement (43%), followed by submandibular space (27%) and Ludwig's angina (17%) (5), Kataria study that showed Ludwig's angina (28.9%) as the most common infected site, followed by peritonsillar abscess and submandibular abscess (10), Mumtaz study in which parapharyngeal space was seen in 20 patients (43.4%) and was at top of the list (21), and the study by YeganehMoghadam that reported peritonsillar (28.7%) and submandibular (21.2%) as the most common sites of infection (12).…”
Section: Discussionsupporting
confidence: 92%
“…Infections of masticator space, retropharyngeal space and parotid space were approximately 7% of our study. Our results were consistent with Meher (9) and Rega (20) with submandibular space as the most common location of DNSI in 37% and 30% of the patients. Our results were not consistent with following studies: Parhiscar study in which parapharyngeal space had the most involvement (43%), followed by submandibular space (27%) and Ludwig's angina (17%) (5), Kataria study that showed Ludwig's angina (28.9%) as the most common infected site, followed by peritonsillar abscess and submandibular abscess (10), Mumtaz study in which parapharyngeal space was seen in 20 patients (43.4%) and was at top of the list (21), and the study by YeganehMoghadam that reported peritonsillar (28.7%) and submandibular (21.2%) as the most common sites of infection (12).…”
Section: Discussionsupporting
confidence: 92%
“…Neck pain was most common symptom seen in 47 (90.38%) patients which was similar to that demonstrated in other studies. 7,8,11,12 In a study by Kamath et al, dysphagia or odynophagia was most common symptom present in 66% followed by pain in neck in 59%. 13 Etiology of deep neck space infections varies depending upon the space involved.…”
Section: Discussionmentioning
confidence: 99%
“…Submandibular abscess is the most common presentation in studies done by Parhiscar et al, Zamiri et al, Meher et al with 28%, 32% and 37% involvement respectively. 10,19,20 The diagnosis of deep neck spaces infections is through clinical examination. It is supplemented by ultrasonography, x-ray and FNAC.…”
Section: Discussionmentioning
confidence: 99%
“…1 There is confusion about the number of neck spaces that varies [13][14][15][16][17][18][19][20]. A fascial space is an area of loose connective tissue bounded by dense connective tissue called fascia.…”
Section: Introductionmentioning
confidence: 99%